Análisis secuencial durante el intervalo Barremiense-Aptiense en la Cubeta de Oliete. - Meléndez, Alfonso; Preat, A.; Soria, Ana Rosa; Vennin, E. (Cuadernos de Geología Ibérica, 1993)
The lower Cretaceous (Upper Barremian-Upper Aptian) marine sediments of the Oliete basin (NE Spain) were traditionnally grouped in the Alacón limestone Formation, Forcalí man Formation and Oliete limestone Formation. Ihe identification of several discontinuities of regional extend allows us to establish ibree dispositional sequences for this sedimentary record which are tentatively correlated with the sequences Late Barremian (Kl.'?), Early Aptian (KI.8) and Late Aptian (K1.9) defined in the Maestrazgo adyacent basin. Further subdivision of these sequences in system tracts was based on extensive facies and microfacies analysis. In the lower sequence lowstand, transgressive and highstand system tract were identified while only transgressive and highstand systems 1 act were recognized for the upper two sequences. Key-Words: Early Cretaceous, Barremian, Aptian, Oliete sub-basin, Ramp, Sequence Stratigraphy.